2020
DOI: 10.1097/der.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Contact Allergens in Best-Selling Ophthalmic Products

Abstract: BackgroundOphthalmic products are a common but often overlooked contributor to allergic contact dermatitis. Frequency of allergenic ingredients in over-the-counter ophthalmic products has not been well characterized.ObjectiveThe purpose of this study was to determine the prevalence of allergenic ingredients in most commonly bought eye lubricants and contact lens solutions.MethodsA product list of Amazon.com's best-selling ophthalmic products was curated by searching for “Best Sellers in Eye Drops, Lubricants &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…A recent report found that more than 30% of top-selling OTC eye lubricant products contained benzalkonium chloride. 3 In our study, benzalkonium chloride was most prevalent in antiglaucoma (88.9%, 80/90), steroid (81.5%, 22/27), and antibiotic (68.2%, 58/85) agents. Topical ophthalmic ointments were typically free from this preservative; other benzalkonium chloride-free formulations are listed in Table 3.…”
Section: Benzalkonium Chloridementioning
confidence: 47%
See 3 more Smart Citations
“…A recent report found that more than 30% of top-selling OTC eye lubricant products contained benzalkonium chloride. 3 In our study, benzalkonium chloride was most prevalent in antiglaucoma (88.9%, 80/90), steroid (81.5%, 22/27), and antibiotic (68.2%, 58/85) agents. Topical ophthalmic ointments were typically free from this preservative; other benzalkonium chloride-free formulations are listed in Table 3.…”
Section: Benzalkonium Chloridementioning
confidence: 47%
“…The NACDG data estimate the prevalence of propylene glycol allergy in patients referred for patch testing to be 2.8% to 4.0% 20 . Propylene glycol was found to be the second highest (12.7%, 13/102) ACDS Core 90 allergen/cross-reactor present in the best-selling OTC eye lubricants and contact lens solutions 3 . We found propylene glycol most frequently in antiglaucoma medications (3.3%, 3/90).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In Europe, positivity to BAC associated with eye drops is estimated to be 1.1% 5 . A recent ingredient analysis of US products found that roughly one‐third of top selling OTC eye lubricants contained BAC; other common allergens were propylene glycol, sorbic acid, amidoamine, and sorbitan sequioleate 7 . Reactions to BAC should be interpreted carefully because of its propensity to cause irritation when patch tested 8 .…”
Section: Discussionmentioning
confidence: 99%